Prevalence, awareness, treatment, and control of hypertension in China data from the China National Nutrition and Health Survey 2002 - Wu, Y.; Huxley, Rachel; Li, L.; Anna, V.; Xie, G.; Yao, C.; Woodward, M.; Li, X.; Chalmers, J.; Gao, R.; Kong, L.; Yang, X. (Lippincott Williams & Wilkins, 2008)
The present article aims to provide accurate estimates of the prevalence, awareness, treatment, and control of hypertension in adults in China. Methods and Results-Data were obtained from sphygmomanometer measurements and an administered questionnaire from 141 892 Chinese adults =18 years of age who participated in the 2002 China National Nutrition and Health Survey. In 2002, ˜153 million Chinese adults were hypertensive. The prevalence was higher among men than women (20% versus 17%; P<0.001) and was higher in successive age groups. Overall, the prevalence of hypertension was higher in urban compared with rural areas in men (23% versus 18%; P<0.01) and women (18% versus 16%; P<0.001). Of the 24% affected individuals who were aware of their condition, 78% were treated and 19% were adequately controlled. Despite evidence to suggest improved levels of treatment in individuals with hypertension over the past decade, compared with estimates from 1991, the ratio of controlled to treated hypertension has remained largely unchanged at 1:4. Conclusions-One in 6 Chinese adults is hypertensive, but only one quarter are aware of their condition. Despite increased rates of blood pressure-lowering treatment, few have their hypertension effectively controlled. National hypertension programs must focus on improving awareness in the wider community, as well as treatment and control, to prevent many tens of thousands of cardiovascular-related deaths. © 2008 American Heart Association, Inc.